Knowledge, Attitudes, Risk Perceptions, and Practices of Spanish Adolescents Toward the COVID-19 Pandemic: Validation and Results of the Spanish Version of the Questionnaire - Aguilar-Latorre, Alejandra; Asensio-Martínez, Ángela; García-Sanz, Olga; Oliván-Blázquez, Bárbara (Frontiers in Psychology, 2022)
Background: During the COVID-19 pandemic, the acquisition of preventive behaviors has been relevant and during adolescence there is usually little perception of risk. Therefore, the objective is to validate, in Spanish, the questionnaire of the knowledge, attitudes, risk perceptions, and practices of adolescents toward the pandemic, and analyze it according to sociodemographic characteristics. Method: A descriptive, cross-sectional study in adolescents between 12 and 18 years of age (n = 354). First, a translation and a back-translation of the questionnaire were performed. Reliability and validity analyses were then carried out and the relationship between the different sociodemographic variables was analyzed. Results: The ordinal alpha obtained was 77%. Knowledge was higher in women, and in those with a higher level of education; and were lower in those who lived in smaller towns, as well as in those who had a member of their family receiving financial aid. In terms of attitudes and risk perceptions, younger adolescents had higher scores, and those who had a member of their family receiving financial aid, lower. Conclusions: The questionnaire is a reliable and valid tool in the Spanish adolescent population. In general, the knowledge about COVID-19 is quite small, however, the practices observed are more appropriate.